Late Renal Effects of COVID-19 in Kidney Transplant Recipients: A Single-Center Study - Gomes, Bruno Teixeira (2025)
Introduction:  During the coronavirus disease 2019 (COVID-19) pandemic, kidney transplant recipients had higher rates of hospitalization and mortality. However, data on the late renal effects of the infection are scarce. Objectives:  This study aims to describe the evolution of renal function and proteinuria in kidney transplant recipients after the infection. Methods:  Single-center prospective cohort study. A total of 321 kidney transplant recipients who survived COVID-19 from March 2020 to December 2022 were included. Data on renal function, proteinuria, and immunosuppression were analyzed pre-infection, 3 and 6 months post-infection. Results:  Most patients were male (58.9%), with a mean age of 50 years, recipients of kidneys from deceased donors (79.4%), and with a median time after transplant of 6.6 years. There was a reduction in the level of immunosuppression, from a pre-infection Vasudev score of 4.66 to 4.50 (p< 0.001) in the 3rd month and 4.54 (p = 0.016) 6 months post-infection. The glomerular filtration rate (GFR) remained stable at around 60 mL/min/1.73 m2. The percentage of patients with proteinuria ≥ 1.0 increased from 9.6% pre-infection to more than 13% (p < 0.001) in the 3rd and 6th months after infection. Higher proteinuria levels were observed in recipients with longer follow-up post-transplant, previous rejection episodes, lower estimated GFR, and higher prevalence of donor-specific anti-HLA antibodies. Conclusions:  Kidney transplant recipients with COVID-19 had an increase in proteinuria within 6 months after the infection despite a stable GFR.